Living voice and lifeless letters: Reserve towards writing in the Graeco-Roman world - Botha, P. J. J. (Hervormde teologiese studies, 1993)
This study contributes to the understanding of communication in antiquity by analysing a few specific references to oral and literate traditions in Hellenistic and Christian texts. In the Graeco-Roman world we find a surprising widespread reticence towards writing, varying from mere indifference to active scepticism. The scribal culture of antiquity exhibits a strong bias towards orality, with even literates expressing little confidence in writing. There was a prevailing preference for the ‘living voice’ in education, and a strong belief that corpora of teaching which were never written down, and could not be written down, distinguished the insiders from the outsiders.